The Role of Multidisciplinary Approaches in Public Health Research: A Literature Review - Yahya, Fajar Dhini (Advances in Healthcare Research, 2023)
Purpose: This article aims to describe the role of multidisciplinary approaches in public health research through a literature review. Method: This research uses a literature review approach to analyze articles relevant to this topic. Various literature sources, including scientific journals, books, and research reports, have been systematically reviewed to obtain pertinent information. Findings: The results demonstrated that a multidisciplinary approach in public health research plays a crucial role in understanding and addressing various health issues. This approach involves collaboration among multiple disciplines, including the social sciences, natural sciences, health sciences, and medical sciences. Through this approach, researchers can gain a comprehensive view of health problems and develop more effective solutions. Implication: This article offers a deeper understanding of the crucial role of multidisciplinary approaches in public health research. Through this approach, researchers can examine health issues holistically and produce findings that are both relevant and impactful for society.